Adaption of Learner Centric Methods in Engineering Education - Maste, Deepali; Kallurkar, Shrikant; Nemade, P. N. (Journal of Engineering Education Transformations, 2015)
There is a change in Face of education through new technologies and teaching and learning process. Also we expect change in education system through technological innovations in daily education activities. Learning platforms, software tools and various monitoring techniques are being developed to support the different stages of education. We face the challenge of monitoring changes in technologies and ways to deliver it to the learners. Educators should keep abreast of technological advancements that support innovations and improvements in instructional design and delivery. Atharva college of Engineering at Mumbai is committed to the mission of creating awareness among students and providing them with a unique opportunity to learn various techniques in formulating IT strategy, helping them keep abreast of the latest technologies in various avenues. Atharva college want to yield education in new and unconventional way and through innovation so we can meet the challenges of improved efficiency, lower costs, increasing accessibility and greater success in achieving development goals. It constantly strives and provide comprehensive technological education in a healthy learning environment, nurturing technocrat leaders for the competitive world. Our college believes in entrepreneurship which need the qualities like capacity and willingness to develop, organize and manage a business venture along with any of its risks in order to make a profit. The college has tried many innovative projects to improve teaching - learning process and develop curiosity in the mind of students. Some of the projects are Satellite Ground station, IEDC, IUCEE - SPEED, Techithon, IEEE, CSI, Paradigm of Life, etc. An opinion survey with sample of students about sense of satisfaction was carried out and presented in the paper with statistical analysis. The findings are useful to take new direction for working at our college along with providing inputs for interested colleges.